Cybersecurity in Learning Systems: Data protection and privacy in educational information systems and digital learning environments - Watini, Sri; Davies, George; Andersen, Nicole (International Transactions on Education Technology (ITEE), 2024)
This research addresses the growing cybersecurity challenges within educational information systems and digital learning platforms, focusing on the protection of sensitive data and user privacy. The objective is to identify prevalent cybersecurity threats in these environments and propose effective solutions to mitigate them. A mixed-method approach is employed, combining a comprehensive literature review with a survey distributed to IT professionals and educators working in digital learning environments. The findings highlight the increasing sophistication of cyberattacks, including data breaches, phishing, and malware, which compromise the integrity and security of educational data. Moreover, the study reveals a gap in the implementation of robust cybersecurity policies, especially in underfunded educational institutions. The proposed solutions emphasize the integration of advanced encryption methods, multifactor authentication, and regular cybersecurity training for all stakeholders. In conclusion, this research underscores the importance of developing a resilient cybersecurity framework tailored to educational systems, ensuring the protection of both institutional data and the privacy of users, thereby enhancing trust and security in digital learning environments.